EXPERIMENTAL EVIDENCE FOR HIGH NOBLE GAS SOLUBILITIES IN SILICATE MELTS UNDER MANTLE PRESSURES - Schmidt B.C.; Keppler H. (My University, 2002)
The solubilities of Ar and Xe in Fe-free synthetic haplogranitic and tholeiitic melts were experimentally determined in the pressure range of 1-11 GPa and at temperatures between 1500 and 2000°C. Experiments were performed in a piston cylinder apparatus (1-3 GPa) and in a multi-anvil apparatus (2-11 GPa). The noble gas concentrations in the quenched glasses were determined with electron microprobe. As a function of pressure, Ar solubility increases linearly up to about 4-5 GPa where it reaches about 4.0 and 0.8 wt% for the haplogranitic and tholeiitic melt, respectively. At higher pressure the amount of dissolved Ar remains constant, suggesting that some threshold concentration is reached. The Xe solubility in tholeiite melt exhibits a very similar pattern. It increases linearly up to about 6 GPa, where a threshold concentration of 0.8 wt% is reached. A further increase of pressure up to 11 GPa does not result in changes in Xe solubility. The leveling off in noble gas solubility at high pressures may imply that the interstitial sites in the melt structure, suitable for the accommodation of noble gas atoms, are fully occupied. Indeed, the experimental data can be successfully reproduced with the Langmuir isotherm, implying a solubility model in which the gas atoms occupy a certain population of interstitial sites. However, the data can be equally well described by a model assuming mixing of the noble gas atoms with the oxygen atoms of the silicate melt. From a thermodynamic point of view, the constant noble gas solubility at high pressures simply implies that the partial molar volumes of the respective noble gas in the fluid and in the melt are equal. Our results differ from those of Chamorro-Perez et al. [Earth Planet. Sci. Lett. 145 (1996) 97-107; Nature 393 (1998) 352-355] who reported an abrupt, order-of-magnitude drop of Ar solubility in silica and olivine melt at around 5 GPa, suggesting that melt densification results in an abrupt decrease of the hole size distribution. A geochemical consequence of our results is that noble gases remain incompatible elements at pressure conditions covering most of the upper mantle. Therefore partial melting remains an efficient process in extracting noble gases and other volatiles from the Earth's mantle.
Keywords: NOBLE GASES; SOLUBILITY; SILICATE MELTS; HIGH PRESSURE